Pengaruh Good Governance dan Sistem Pengendalian Intern Pemerintah Pada Kinerja Pemerintah Daerah - Putra, I Gede Agus Sudiarsana; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2018)
The government as an agent of the community is required to be able to account for its performance. Good performance can be seen from the implementation of good governance and the government's internal control system in a government agency. This study aims to determine whether there is an influence of the Good Governance and the Government Internal Control System on the Performance of the Regional Government of Karangasem Regency. The study was conducted at the Government of Karangasem Regency by making 152 officials scattered in 38 Regional Device Organizations (OPD), with purposive sampling method. Based on the results of the analysis, it is known that Good Governance and the Government's Internal Control System have positive influence on the Performance of the Government of Karangasem Regency, meaning that the better the implementation of good governance and the government's internal control system, the better the Performance of the Karangasem District Government. Keywords :  Good governance, internal control system, government performance.